2021
DOI: 10.1111/add.15565
|View full text |Cite
|
Sign up to set email alerts
|

Methadone and buprenorphine treatment in United States jails and prisons: lessons from early adopters

Abstract: Aims To identify implementation barriers and facilitators to the adoption and implementation of programs that provide opioid agonist treatments (OAT) with methadone and buprenorphine to treat opioid use disorder in jails and prisons in the United States. Design Qualitative analysis: semi‐structured interviews were conducted and thematic analyses of transcripts and notes were performed using a hybrid inductive/deductive coding approach. Setting Jails and prisons in the United States. Participants From August 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…Another possibility is that individuals receiving MMT begin to feel more favorably toward the prison administration over time as they interact with them on a daily basis, since MMT requires daily exposure to the prison administration. A plausible explanation for this increased favorability is that the medical personnel providing MMT in Moldovan prisons may begin to relinquish stigmatizing attitudes toward methadone as they continue to provide this treatment, a pattern that other studies have observed in prison settings elsewhere (Bandara et al, 2021).…”
Section: Interactions With Formal Administration Discourage Mmt Uptakementioning
confidence: 95%
“…Another possibility is that individuals receiving MMT begin to feel more favorably toward the prison administration over time as they interact with them on a daily basis, since MMT requires daily exposure to the prison administration. A plausible explanation for this increased favorability is that the medical personnel providing MMT in Moldovan prisons may begin to relinquish stigmatizing attitudes toward methadone as they continue to provide this treatment, a pattern that other studies have observed in prison settings elsewhere (Bandara et al, 2021).…”
Section: Interactions With Formal Administration Discourage Mmt Uptakementioning
confidence: 95%
“…Years of public health advocacy around this issue [ 10 ], along with several lawsuits against correctional facilities that refused to provide MOUD in the midst of a worsening opioid epidemic [ 11 ], have pushed jurisdictions around the country to increase access to MOUD in correctional settings. Despite initial success in some model states such as Rhode Island [ 12 ] much remains to be learned about addressing implementation challenges related to acceptance, adoption and sustainability of MOUD behind bars and upon release [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Local jails experience particular challenges to implementing MOUD programs [ 13 ]. Unlike prisons, jails are typically overseen by local governments and primarily house persons awaiting trial who cycle rapidly through them, often with unpredictable lengths of stay.…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, new patients wishing to initiate methadone treatment were faced with this barrier in 20% of clinics (19). Similarly, prior to the pandemic, both methadone and buprenorphine-based OTPs were found to be effective in US jails and prisons; however, following the pandemic, these OTPs have been discontinued (20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, new patients wishing to initiate methadone treatment were faced with this barrier in 20% of clinics (19). Similarly, prior to the pandemic, both methadone and buprenorphine-based OTPs were found to be effective in US jails and prisons; however, following the pandemic, these OTPs have been discontinued (20-21). Together, it is very important to examine the changes in methadone distribution during the COVID-19 pandemic and determine whether there are regional disparities in access to this evidence-based pharmacotherapy.…”
Section: Introductionmentioning
confidence: 99%